Fabrication of Spherical Colloidal Supraparticles via Membrane Emulsification - Parinamipura Mahadevappa, Naveen Kumar; Römling, Lea; Sultan, Umair; Vogel, Nicolas (Langmuir, 2024)
Colloidal supraparticles are micrometer-scale assemblies of primary particles. These supraparticles have potential application in photonic materials, catalysis, gas adsorption, and drug delivery. Thus, the synthesis of colloidal supraparticles with a narrow size distribution and high yield has become essential. Here, we demonstrate membrane emulsification as a high-throughput approach for fabricating spherical supraparticles with a narrow size distribution and control over particle size and crystallinity. Spherical supraparticles with well-ordered surface structures are synthesized by generating emulsion droplets of an aqueous colloidal dispersion in fluorocarbon oil using a Shirasu porous glass membrane followed by the consolidation of particles through water removal within the emulsion. We systematically investigate process parameters, including the flow rate of the particle dispersion, the particle concentration, and the average pore diameter of the membrane, on the mean size and size distribution of the supraparticles, revealing key factors governing supraparticle properties and production throughput. A comparative evaluation with commonly employed methods highlights the advantage of membrane emulsification, which combines well-defined internal structure and controlled supraparticle sizes with comparably high yields on the order of tens of grams per day. Importantly, in contrast to widely used droplet-based microfluidics, membrane emulsification allows fabrication of supraparticles in nonfluorinated oil. Overall, membrane emulsification offers a simple yet versatile method for fabricating colloidal supraparticles with high quality and yield and may serve as a bridge between existing high-precision techniques, such as droplet-based microfluidics, and high-throughput processes with less control, such as spray-drying.
CRIS-Team Scopus Importer:2024-10-25
Keywords: Colloidal particles; Emulsification; Emulsions; Liquids; Membranes